STUDENTS’ PERCEPTION OF BLENDED LEARNING IN UNIVERSITY INSTITUTION: A CASE STUDY OF THE STUDENTS AT ENGLISH DEPARTMENT OF PGRI UNIVERSITY - Santoso Santoso; Herlina Herlina (Esteem Journal of English Education Study Programme, 2023)
Due to a scope and scale with the main focus on social presence this research is aimed at exploring social presence, students’ perceptions of social presence and the implementation blended learning. The research was employed as mixed method research approach along with a questionnaire. The main objective included determination of English as Foreign language students’ perception of blended learning by participants’ including a total of 73 judgmental statement clauses. Also this study was helped by 17 students as the voluntary interviews. The findings of this study were derived from the results obtained through the questionnaire and interviews among students with a conclusion that most of the students strongly appreciated the blended learning of social presence in increasing interaction among members and improving writing and speaking exercise activities. However there was no big distinction in social presence between a blended learning class and a traditional face-to-face class. And among factors that affect social presence the students ranked the top three important factors including the lecturer closeness and humor and his/her feedback work. Also the list have three important ones which are shorter forum discussions and peer feedback.